Normal Immunostaining Pattern for Aquaporin-5 in the Lesions of Palmoplantar Hyperhidrosis - Kyoko Nakahigashi; Takashi Nomura; Yoshiki Miyachi; Kenji Kabashima (Karger Publishers, 2013)
Aquaporin-5 (AQP-5) is a water-transporting protein expressed in mammal sweat glands. It has been reported that the expression of AQP-5 is involved in sweating of mice, rats, and horses. However, the physiological function of human AQP-5 is still uncertain. In this report, we examined the expression pattern of AQP-5 in the skin lesions of palmoplantar hyperhidrosis in patients with Nagashima-type palmoplantar hyperkeratosis (PPK). We found that there was no significant difference in AQP-5 expression in the palmoplantar skin of healthy subjects and patients with palmoplantar hyperhidrosis. Our findings suggest that a mechanism other than AQP-5 may be involved in the pathogenesis of hyperhidrosis in PPK.